2022
DOI: 10.3389/fimmu.2022.816952
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation Attenuates Neurotoxic Polarization of Macrophages by Inhibiting the Notch1-HIF-1α/NF-κB Signalling Pathway in Mice With Spinal Cord Injury

Abstract: Spinal cord injury (SCI) is a catastrophic disease with a complex pathogenesis that includes inflammation, oxidative stress, and glial scar formation. Macrophages are the main mediators of the inflammatory response and are distributed in the epicentre of the SCI. Macrophages have neurotoxic and neuroprotective phenotypes (also known as classically and alternatively activated macrophages or M1 and M2 macrophages) that are associated with pro- or anti- inflammatory gene expression. Our previous study demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
0
19
2
Order By: Relevance
“…Our group has developed an implantable optical fiber so that laser bioenergy could directly reach the surface of the spinal cord ( Wang et al, 2021a ; Wang et al, 2021b ; Ma et al, 2022 ). Compared with percutaneous irradiation, there is no skin or muscle barrier, which improves the efficacy of PBM.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has developed an implantable optical fiber so that laser bioenergy could directly reach the surface of the spinal cord ( Wang et al, 2021a ; Wang et al, 2021b ; Ma et al, 2022 ). Compared with percutaneous irradiation, there is no skin or muscle barrier, which improves the efficacy of PBM.…”
Section: Discussionmentioning
confidence: 99%
“…M1-type microglia/macrophages in the acute stage after spinal cord injury can continuously release inflammatory chemotactic mediators and pro-inflammatory cytokines, causing great pressure on the survival of neurons [ 7 , 25 ]. Spinal cord tissues collected 3 days post-surgery were stained with iNOS/Iba1 or Arg-1/Iba1 to evaluate the polarization of microglia/macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…It has been verified by a handful number of reports that Ang-(1–7) can regulate inflammation and alleviate oxidative stress, and ischemia–reperfusion in the local environment of brain, kidney, heart, liver, lung, and joints [ 20 , 55 – 58 ]. Recent clinical longitudinal studies have shown that Ang-(1–7) is locally upregulated after mild traumatic brain injury in humans, and that Ang-(1–7) gradually decreases as inflammation subsides in mTBI patients: this can be viewed as an attempt to balance pro-inflammatory and anti-inflammatory events [ 25 ]. Research by Ruili Dang et al showed that Activation of the ACE2/Ang(1–7)/MasR axis triggers the Forkhead box Class O1 (FOXO1) -autophagy pathway and induces FoxO1-targeted superoxide dismutase (SOD) and catalase (CAT) of microglia for neuroprotective effects [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested that different wavelengths of PBM have significant regulatory effects on osteoblast differentiation [14]. We had previously applied PBM to the therapy of spinal cord injury and found that PBM could reduce the inflammatory response, reduce oxidative stress, inhibit neuronal apoptosis, and promote repair of spinal cord injury functions [31][32][33]. Although oxidative stress is one of the main inhibitors of osteoblast differentiation, PBM regulates osteoblast proliferation.…”
Section: Discussionmentioning
confidence: 99%